Cellular Neural Networks design for sensor networks. - João Luís Fernandes Ferreira (2021)
The concept of Cellular Neural Networks was proposed by Leon O. Chua and Lin Yang in 1988, and it has ever since seen only relatively modest but promising improvements. The goal of this work is to delve further into this subject, which we consider to be largely unexplored, and to try to make a positive contribution to it. We also consider that these advancements fill an important gap in the context of the recent breakthrough we have been witnessing in the field of artificial intelligence and data fusion.